Risk of celiac disease, type 1 diabetes, and thyroid disease autoimmunity during the SARS-CoV-2 pandemic in South of Sweden: insights from the TRIAD study - Alexander Lind; Maria Naredi Scherman; Samia Hamdan; Daniel Agardh (Autoimmunity)
Recent studies have implied an increased incidence of autoimmune diseases following the SARS-CoV-2 pandemic. The objective was to determine if SARS-CoV-2 infections were associated with celiac disease (CD), type 1 diabetes (T1D), and autoimmune thyroid disease (AITD) autoantibodies in a population-based screening when the pandemic hit the South of Sweden during 2021 and 2022. Between August 2021 and June 2022 self-obtained capillary plasma samples were collected from 1088 children at 6–9 years of age and 1185 adolescents at 13–16 years of age, who were randomly invited from the general population to a screening for CD, T1D, AITD, and SARS-CoV-2 antibodies. Among children and adolescents screened for autoantibodies associated with CD, T1D and AITD, the SARS-CoV-2 infection rate was increased in tissue transglutaminase autoantibody (tTGA) positive (13/17; 76.5%) compared with tTGA negative (492/1168; 42.1%) 13–16-year-old individuals (p = 0.0057). There was no association between SARS-CoV-2 infection rate and AITD- or T1D autoantibodies. Our findings indicate a potential association between prior SARS-CoV-2 infection and screening-detected CD autoimmunity in adolescents aged 13–16 years. Further research is needed to elucidate whether ongoing CD autoimmunity increases susceptibility to infection or if SARS-CoV-2 may act as a trigger for CD autoimmunity in genetically and environmentally predisposed individuals.